Epoxidation of 1,5,9-Cyclododecatriene with Hydrogen Peroxide over Ti-MCM-41 Catalyst - Agnieszka Wróblewska (MDPI AG, 2021)
This work presents the results of our research on the epoxidation of 1,5,9-cyclododecatriene (CDT) with hydrogen peroxide over the Ti-MCM-41 catalyst. The influence of the following parameters on the course of the process was investigated: temperature, CDT:H2O2 molar ratio, solvent composition and its type, and catalyst content. The highest selectivity of CDT transformation to 1,2-epoxy-5,9-cyclododecadiene (ECDD)—approximately 100 mol%, the highest yet reported—was obtained at the CDT conversion of 13 mol% and with the following parameter values: a catalyst content of 5 wt%; a molar ratio of CDT:H2O2 = 2; isopropyl alcohol (i-PrOH) as the solvent, with a composition of 80 wt% in the reaction mixture; a temperature of 80 °C; and a reaction time of 240 min. The highest conversion of CDT (37 mol%) was obtained at the ECDD selectivity of 56 mol% and using the following process parameters: a catalyst content of 5 wt%; a molar ratio of CDT:H2O2 = 0.5; i-PrOH used as the solvent, with solvent composition of 80 wt%; a temperature of 80 °C; and a reaction time of 60 min. It should be emphasized that the CDT conversion obtained in the current study is higher (by 9 mol%) than that described in the literature on heterogeneous catalysts.